ACR Appropriateness Criteria ® Urinary Tract Infection-Child - Karmazyn, Boaz K; Alazraki, Adina L; Anupindi, Sudha A; Dempsey, Molly E; Dillman, Jonathan R; Dorfman, Scott R; Garber, Matthew D; Moore, Sheila G; Peters, Craig A; Rice, Henry E; Rigsby, Cynthia K; Safdar, Nabile M; et al. (Journal of the American College of Radiology, 2017)
Urinary tract infection (UTI) is common in young children and may cause pyelonephritis and renal scarring. Long-term complications from renal scarring are low. The role of imaging is to evaluate for underlying urologic abnormalities and guide treatment. In neonates there is increased risk for underlying urologic abnormalities. Evaluation for vesicoureteral reflux (VUR) may be appropriate especially in boys because of higher prevalence of VUR and to exclude posterior urethral valve. In children older than 2 months with first episode of uncomplicated UTI, there is no clear benefit of prophylactic antibiotic. Ultrasound is the only study that is usually appropriate. After the age of 6 years, UTIs are infrequent. There is no need for routine imaging as VUR is less common. In children with recurrent or complicated UTI, in addition to ultrasound, imaging of VUR is usually appropriate. Renal cortical scintigraphy may be appropriate in children with VUR, as renal scarring may support surgical intervention. The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer reviewed journals and the application of well-established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness of imaging and treatment procedures for specific clinical scenarios. In those instances where evidence is lacking or equivocal, expert opinion may supplement the available evidence to recommend imaging or treatment.